Hybrid Architecture for Coordination of AGVs in FMS. (14th March 2014) - Hernandez-Martinez, Eduardo G.; Foyo-Valdes, Sergio A.; Puga-Velazquez, Erika S.; Meda-Campaña, Jesús A.
This paper presents a hybrid control architecture that coordinates the motion of groups of automated guided vehicles in flexible manufacturing systems. The high-level control is based on a Petri net model, using the industrial standard ISA-95, obtaining a task-based coordination of equipment and storage considering process restrictions, logical precedences, shared resources and the assignment of robots to move workpieces individually or in subgroups. On the other hand, in the low-level control, three basic control laws are designed for unicycle-type robots in order to achieve desired formation patterns and marching behaviours, avoiding inter-robot collisions. The control scheme combines the task assignment for the robots obtained from the discrete-event model and the implementation of formation and marching continuous control laws applied to the motion of the mobile robots. The hybrid architecture is implemented and validated for the case of a flexible manufacturing system and four mobile robots using a virtual reality platform.